Economics and Ageing Volume I: Theory - Iparraguirre, José Luis (Springer International Publishing, 2018)
This upper level textbook provides a coherent introduction to the economic implications of individual and population ageing. Placing economic considerations into a wider social sciences context, this is ideal reading not only for advanced undergraduate and masters students in economics, health economics and the economics of ageing, but also policy makers, students, professionals and practitioners in gerontology, sociology, health-related sciences and social care. This volume introduces the different conceptualisations of age and definitions of `old age', as well as the main theories of individual ageing as developed in the disciplines of biology, psychology and sociology. It covers the economic theories of fertility, mortality and migration and describes the four main frameworks that can be used to study economics and ageing, namely the life cycle, the overlapping generations, the perpetual youth and the dynastic models. José Luis Iparraguirre is Chief Economist at Age UK and Professor of Economics at the University of Morón, Buenos Aires, Argentina. .